Sovereign wealth funds 2021 : Changes and challenges accelerated by the Covid-19 Pandemic - Capapé, Javier (IE University, 2022)
It has now been nearly two years since the onset of the coronavirus pandemic. Vaccine development and active public health campaigns have delivered us to the threshold of a return to “normal”, even as we struggle to reimage its definition. In the wake of the immediate onset of the crisis, sovereign investment slowed dramatically consistent with an abrupt halt to an economic activity generally. As interest rates continued to decline and public market equity valuations recovered in 2020, the pace of global M&A activity also rebounded with quarterly deal counts returning to late-2019 levels by Q4 2020. In the intervening period, deal activity remained robust in depth, breadth, and velocity, as 2021 ended with record volumes and values. This transformation has paralleled the growth in direct sovereign investment activity that we have tracked and studied since 2010 and continues to feature prominently in the direct investing activity of the sovereign investors whose recent deals comprise of our current sample. Not surprisingly, and quite as usual, prior patterns – participating funds, volumes, geographies, and even co-investment practices – persist. However, the five quarters that constitute our current student have been anything but “normal”. Our current sample includes direct sovereign equity investments announced between October 2020 and December 2021. Our coverage includes 418 investments across 448 discrete deals with the difference attributable to investments in which sovereign funds invested in the same deal. Thus, our current sample is nearly 3 times larger than our 2019-20 sample and on average considerably larger than any prior sample. We track the investment activity of 40 SWFs. Similarly to previous reports, activity was dominated by the top 5. These include Temasek who comprise 27.9% of investment activity, GIC, Mubadala, the Qatar Investment Authority, and the Abu Dhabi Investment Authority. This group of five together represent approximately 23% of the funds included in our sample, but over 85% of the investments. For our current sample, SWFs participated in transactions whose aggregate transaction value was approximately $120 billion.
Keywords: Sovereign wealth funds; Economic growth; Crecimiento económico; Post-pandemic economy; Ecomomía post-pandemia; Public market equity valuation; Public Health; Salud Pública